2007
DOI: 10.1161/circresaha.106.141986
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Signature and Antisense-Mediated Depletion Reveal an Essential Role of MicroRNA in Vascular Neointimal Lesion Formation

Abstract: Abstract-MicroRNAs (miRNAs) are a recently discovered class of endogenous, small, noncoding RNAs that regulate about 30% of the encoding genes of the human genome. However, the role of miRNAs in vascular disease is currently completely unknown. Using microarray analysis, we demonstrated for the first time that miRNAs are aberrantly expressed in the vascular walls after balloon injury. The aberrantly expressed miRNAs were further confirmed by Northern blot and quantitative real-time polymerase chain reaction. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
852
1
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 856 publications
(902 citation statements)
references
References 41 publications
34
852
1
6
Order By: Relevance
“…miR-195 was reported to be up-regulated in cardiac hypertrophy, and transgenic mice overexpressing miR-195 resulted in cardiac growth with disorganization of cardiomyocytes [35]. Ji et al [36] reported that miR-195 was highly expressed in rat carotid artery and down-regulated in the process of wound healing caused by balloon injury (see its supplemental data). The Neurogenin3 transcript is targeted by miR-195, which contributes to islet cell regeneration in pancreas [37].…”
Section: Discussionmentioning
confidence: 99%
“…miR-195 was reported to be up-regulated in cardiac hypertrophy, and transgenic mice overexpressing miR-195 resulted in cardiac growth with disorganization of cardiomyocytes [35]. Ji et al [36] reported that miR-195 was highly expressed in rat carotid artery and down-regulated in the process of wound healing caused by balloon injury (see its supplemental data). The Neurogenin3 transcript is targeted by miR-195, which contributes to islet cell regeneration in pancreas [37].…”
Section: Discussionmentioning
confidence: 99%
“…This team identified p27 (Kip1) and p57 (Kip2) as potential targets for these miRNAs in these cells. Further by knocking down miR-221 and miR-222 in rat carotid arteries, they revealed therapeutic potential for these miRNAs in suppressing cell proliferation in vivo and neointimal lesion formation after angioplasty [149,150]. The role of miRNAs in regulating endothelial cells in response to hypoxia was also studied [151].…”
Section: Mirnas and Cardiovascular Diseasesmentioning
confidence: 99%
“…In keeping with their roles in cell proliferation, miRs are key participants in neointimal development. Arterial injury leads to rapid differential expression in miRs, with up-regulation of miR-21, miR-146, miR-214 and miR-352, and down-regulation of miR-125a, miR-125b, miR-133a, miR-145, miR-143, miR-347 and miR-365 [71]. Antisense knockdown of the most up-regulated of these (miR-21) reduces neointima, again suggesting that manipulation of single miRs has the potential for therapeutic benefit.…”
Section: Micrornas: Small But Powerful Controllers Of Cardiac Developmentioning
confidence: 99%